Good agricultural practices (GAP) to improve rice productivity in Uganda - CGIAR Research Program on Rice (2021)
The GAP technologies tested in Doho region of Uganda. Yield increased from 3.1 to 4.64 t/ha. The GAP technologies were out scaled in Uganda through TAAT project in 2019. More than 5000 farmers trained by private sector.